LA ENSEÑANZA DE LOS ESTUDIOS SOCIALES Y LA EDUCACIÓN CÍVICA: HACIA UNA PROFESIÓN INTERDISCIPLINAR - Agüero García, Javier (2025)
This paper analyzes the profession in the Enseñanza de los Estudios Sociales y la Educación Cívica in the context of the reform of the curriculum offered by the escuelas de Historia, Geografía and Formación Docente, of the University of Costa Rica. Primary sources to contextualize this career involved the analysis of books, essays, official documents, and the existing curriculum. We analyze the constitution of the profession from 1951 until today. Also, the external context is explained according to international trends in the Enseñanza de los Estudios Sociales y la Educación Cívica and so is studied the national context. We identify and confront the different offers in higher education in both, public and private sectors trying to determine the objectives, organizational structure, graduate profile and occupational field. Finally, we consider updating the curriculum in the Enseñanza de los Estudios Sociales y la Educación Cívica at the University of Costa Rica to be an urgent task because changes in higher education and social demands require public universities to offer appropriate, flexible curricular offerings according to social and cultural needs.